Ovarian papillary carcinoma in bitch: a case report (Research, Society and Development, 2022)
The current view of pets as family members and the increased of affection dedicated to them, leads to a search for capacited and specialized professionals who can promote techniques and treatments to increase their longevity, especially in cases of advanced cancer, wich can affect various systems of the organism. Reproductive tumors gain a certain enphasis in bitches, mainly because they can have asymptomatic evolution, being discovered at random, as a finding, and often in late stages, as occurs in ovaries neoplasms. Thus, the present study aimed to report a rare case of ovarian papillary carcinoma in bitch, describing clinical alterations, macroscopic characteristics, ultrasound and radiological findings, and histological descriptions. Considering the scarcity of literature and the low prevalence of this type of thumor, this report aims to contribute to the orientation of clinical management, diagnosis and treatment of this pathology.